Privatization and environmental policy in a mixed oligopoly - Bércena-Ruiz, Juan Carlos; Dong, Quan; Garzón, María Bergoña (Estudios de Economía, 2019)
This paper analyzes the interaction between two political economy decisions by a government: whether to privatize a public firm and what environmental policy to choose (an environmental tax or an emission standard). We find that when market competition is weak the government does not privatize the public firm and sets an environmental tax. When it is intermediate the public firm is not privatized and the government sets an environmental standard. Finally, when market competition is strong the government privatizes the public firm and is indifferent between a tax and a standard.